Evaluasi Kegiatan Sosialisasi Produk Impor Halal dan Nonhalal bagi Siswa Madrasah Aliyah Persis 24 Rancaekek Bandung - Akim Akim; Chandra Purnama; Neneng Konety; Febriani Amalina Shalihah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The existence of Indonesia as a country with the largest number of Muslim societies in the world is an allure for foreign producers, coupled with the preference of people who are relatively more interested in imported products resulting in Indonesia's domestic market being flooded with imported products. This condition is a bit dangerous for Muslim consumers when it is associated with the lack of halal awareness in Indonesian society, so that the activities of community awareness are needed, one of which is in the form of socialization activities. This article aims to evaluate the socialization activities carried out among Madrasah Aliyah (Islamic Senior High School) students in Rancaekek Bandung. The socialization activities are carried out using the seminar method in the form of lectures with questions and answers and simulation methods in the form of simulation exercises. Meanwhile, the evaluation of the socialization activities was carried out by conducting pre-test and post-test with the help of IBM SPSS version 21 to measure the effect of socialization on the knowledge of the students of Madrasah Aliyah Persis 24 Rancaekek related to the halal of imported products. From the test results obtained, it can be concluded that the socialization activities carried out succeeded in increasing the knowledge of the students of Madrasah Aliyah Persis Rancaekek regarding the importance of the halal status of imported products circulating in the community.